ANALISIS KEPASTIAN HUKUM ALAT BUKTI PADA PERJANJIAN ELEKTRONIK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Suhartini, Endeh (DERECHTSSTAAT, 2016)
The study, entitled "Analysis of Legal Certainty Evidence In the Treaty Electronics Based on Law No. 11 of 2008 on Information and Electronic Transactions" seeks to answer two formulation of the problem is how the legal certainty of evidence in the agreement electronically based on Law No. 11 Year 2008 on Information and Electronic transactions and the things that are prohibited in the use of Electronic technology is based on Law Number 11 Year 2008 on Information and Electronic transactions ?. The method used is the method of normative legal writing is a writing that examines the application of positive law within the society and protected by law, in addition to writing also uses the method of writing the empirical (sociological). From the studies undertaken are: Legal Certainty of evidence by the Treaty Electronics based on Article 5 of Law No. 11 of 2008 that the Electronic Information and Electronic Documents have legal certainty could be submitted as legal evidence for the interest of the parties in the event of disputes and can be brought to court if the interests require and prohibited the use of technology Electronic Transaction Agreement as provided for in Article 27 and 37 of Law. No. 11 of 2008 on Information and Electronic Transactions is to provide limits and reducing the legal problems that would be detrimental to the party where the effect of the transaction agreement that enabled it to be published data and information can be misused by unscrupulous people who do not responsible. Some of the problems that would be detrimental to them: The presence of Criminal Fraud, extortion, defamation, and the Economic Crime which would be detrimental to the parties as well as the problems of adverse privately and publicly.